2008
DOI: 10.1074/jbc.m707551200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Is a Novel Stimulator of Glucose Uptake and Metabolism in Skeletal Muscle Cells

Abstract: Skeletal muscle plays a major role in glucose and lipid metabolism. Active hepatocyte growth factor (HGF) is present in the extracellular matrix in skeletal muscle. However, the effects of HGF on glucose and lipid metabolism in skeletal muscle are completely unknown. We therefore examined the effects of HGF on deoxyglucose uptake (DOGU), glucose utilization, and fatty acid oxidation (FAO) in skeletal muscle cells. HGF significantly enhanced DOGU in mouse soleus muscles in vitro. Furthermore, HGF significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 35 publications
1
49
1
Order By: Relevance
“…We also observed that the hepatocytes treated with PI3K-specific siRNA and a Akt inhibitor blocked the IL-6-induced increase in GLUT-2 expression and 2-DG uptake which strongly suggests the involvement of PI3K/Akt pathway. Consistently, Perdomo et al (2008) reported that GLUT-4 translocation to the plasma membrane is abolished by wortmannin (PI3K inhibitor) and Akt inhibitor. Recent evidence suggests a link between IL-6 and MAPKs.…”
Section: Discussionmentioning
confidence: 66%
“…We also observed that the hepatocytes treated with PI3K-specific siRNA and a Akt inhibitor blocked the IL-6-induced increase in GLUT-2 expression and 2-DG uptake which strongly suggests the involvement of PI3K/Akt pathway. Consistently, Perdomo et al (2008) reported that GLUT-4 translocation to the plasma membrane is abolished by wortmannin (PI3K inhibitor) and Akt inhibitor. Recent evidence suggests a link between IL-6 and MAPKs.…”
Section: Discussionmentioning
confidence: 66%
“…However, in the context of tumor mitochondrial physiology, suppression of downstream complexes is more consistent with inhibiting biosynthetic pathways necessary for tumorigenic growth. Interestingly, HGF/Met signaling augments glycolytic flux (77); however, we show a significant enhancement of OXPHOS components, potentially to support the cell with increased biosynthetic abilities consummate with the pro-proliferative and pro-angiogenic nature of HGF/Met signaling. These data substantiate a novel anti-tumorigenic role for decorin to compromise mitochondrial capacity (and potentially function) through the concerted suppression of multiple key components of OXPHOS (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Growth factors, including HGF, EGF and TNF-, have been shown to increase glucose utilization in a variety of cells (Bertola et al, 2007;Boussouar and Benahmed, 1999;Hsu and Sabatini, 2008;Perdomo et al, 2008;Véga et al, 2002). Furthermore, Kaplan and colleagues (Kaplan et al, 2000) have shown that HGF also enhances glycolysis and oxidative phosphorylation in murine mammary cells.…”
Section: Hgf Increases Proton Production Inducing Acidification Of Tmentioning
confidence: 99%